Lagari and His Turkish Poems - İçli, Ahmet (Fırat University, 2021)
Magazines/compilations have an important place among the sources of Turkish literature. These works are important that contribute to the history of literature in many ways. The name of a poet, which is about to disappear, can take its place in the sources again, based on the poem found in a magazine. Sometimes it happens that a poem has been accidentally or intentionally recorded on behalf of someone else or is owned by someone else. The classification and content analyzes and general evaluations made on the axis of compilations are important research areas in the context of the determination of poems and poets. Information about Lagari and his poems, one of the poets of classical Turkish literature, can be reached through journals/compilations. There is brief information about a poet with the pseudonym Lagari in a biographical works/tazkeerahs. Since poets have the same pseudonym is one of the handicaps in literary studies, it is possible for Lagari to be as different as the person mentioned in the biographies. It is not a remote possibility that Lagari Hasan, who lived in the 17th century, was also a poet. There are Turkish poems attributed to Lagari in the journal/magazine, some of which are stated to have been compiled by him. Some of these poems are also seen in the poetry books of other poetsOur study is on the axis of determining the poems attributed to Lagari, transferring them to Latin letters, and short evaluations about him and his poems

Mecmualar, Türk edebiyatının kaynakları arasında önemli bir yere sahiptir. Bu eserler, edebiyat tarihine birçok yönden katkı sunan derlemeler niteliğindedir. Bir mecmuada tespit edilen şiirden hareketle kaybolmaya yüz tutmuş bir şairin adı kaynaklardaki yerini alabilmektedir. Kimi zaman bir şiirin başkası adına sehven veya bilinçli bir şekilde kayıtlandığı veyahut başkası tarafından sahiplendiği görülmektedir. Mecmualar ekseninde yapılan tasnif ve muhteva incelemeleri ile genel değerlendirmeler, şiirlerin ve şairlerin tespiti bağlamında önemli araştırma alanlarındandır. Klâsik Türk edebiyatı şairlerinden Lâgarî ve şiirleri hakkındaki bilgilere mecmualar sayesinde ulaşılmaktadır. Şairin kimliği noktasında kesin ve net bilgi yoktur. Ancak Lâgarî hakkında iki tezkirede çok kısa bilgi vardır. Şairlerin aynı mahlası taşımaları edebiyat araştırmalarındaki handikaplardan biri olduğundan Lâgarî’nin tezkirelerde geçen kişi ile aynı olma ihtimali kadar farklı biri olması da mümkündür. Bu yüzyılda yaşamış Lâgarî Hasan Çelebi’nin de şair olması uzak bir ihtimal değildir. Bir bölümünün de Lâgarî tarafından derlendiği ifade edilen mecmuada, Lâgarî’ye atfedilen Türkçe şiirler bulunmaktadır. Bu şiirlerden bazıları, başka şairlere ait divanlarda da görülmektedir. Çalışmamız, Lâgarî’ye atfedilen şiirlerinin tespiti, Latin harflerine aktarımı ile Lâgarî ve şiirleri hakkında kısa değerlendirmeler eksenindedir.
LÂGARÎ VE TÜRKÇE ŞİİRLERİ